Carbon and nitrogen dynamics in ageing earthworm casts in grasslands of the eastern plains of Colombia - Decaëns, Thibaud; Rangel Becerra, Andrés Felipe; Asakawa, N.; Thomas, Richard J. (Springer, 1999)
The effects of a large species of anecic earthworm, Martiodrilus carimaguensis Jiménez and Moreno, on soil C and N dynamics were investigated in a native savanna and a man-made pasture of the eastern plains of Colombia. We compared, across time (11 months), the total C, total N, NH+ 4 and NO– 3 contents in the earthworm casts, the underlying soil and the adjacent soil. Additional sampling of root biomass and macrofauna was performed. In the two management systems, the total C and N contents were higher in casts (4.33–7.50%) than in the bulk soil (2.81–4.08%), showing that the earthworms selected food substrates with high organic contents. In general, C contents significantly increased during cast ageing (+100%), possibly because of CO2 fixation processes, dead root accumulation and/or macrofaunal activities in casts. In fresh casts, NH+ 4 levels were very high (294.20–233.98??g g–1 dry cast) when compared to the soil (26.96–73.95??g g–1 dry soil), due to the intense mineralisation processes that occurred during the transit of soil and organic matter through the earthworm gut. During the first week of cast ageing, NH+ 4 levels sharply decreased, while NH– 3 levels showed successive peaks in the casts, the underlying soil and the adjacent soil. These results suggested the rapid production of NO– 3 by nitrification processes in the fresh casts, followed by diffusion to the nearby soil, first vertically, then horizontally. After 2 weeks of cast ageing, NH+ 4 and NO– 3 levels only showed slight variations, likely because of organic matter protection in stable dry casts. The root biomass was higher (1.6–4.7 times) below the old earthworm casts. The ecological significance of these results is discussed.